(untitled) (Open Herald: Periodical of Methodical Research, 2025)
The present work included a series of steps that can be sequenced into four steps: the first is the conversion of the ester to hydrazide by replacing the O-R group of the ester with the NH-NH2 group. The second and most important is the cyclization reaction to form thiol oxadiazole. The third step is the preparation step for Schiff-Biss reactions by replacing the S-H group with the NH-NH2 group. The fourth and final step is the reaction of hydrazide oxadiazole with aldehyde to form an important functional group in the complexation processes, which is the azomethine group N=CH. The synthesized ligand and the metals nickel (II) and cobalt (II) underwent complexation reactions. Melting point readings and thin layer chromatography(TLC) were used to track the produced compounds’ purity . The suggested chemical structural formulas were validated using mass spectra, 1H-NMR, 13C-NMR, and FT-IR.